The Influence of Perceived Organizational Support and Organizational Justice on Job Satisfaction - Dinda Triwinanti; Fetty Poerwita Sary (International Journal Labs, 2024)
AIESEC is a youth-led global organization that seeks to achieve peace and fulfill human potential by activating leadership qualities among youth. Job satisfaction is seen based on the Net Promoter Score (NPS). This research aims to determine the influence of perceptions of organizational support and organizational justice on job satisfaction at AIESEC Bandung. This research uses a quantitative type of research with a saturated sampling technique. The data collection method was carried out by distributing questionnaires to 157 respondents. The research results were processed and analyzed using descriptive analysis with PLS-SEM analysis techniques. The research results show that organizational support has a significant effect on job satisfaction as well as organizational justice which has a significant effect on job satisfaction.